Uso de sensores remotos para estimar biomasa arriba del suelo en bosques de la Península de Osa - Soto-Montoya, Casia (Instituto Tecnológico de Costa Rica, 2011)
A study using 18 plots from the "Biodiversity Project and Carbon Sequestration in the Forests of Peninsula de Osa" was conducted to estimate above ground forest biomass. The plots correspond to different forest succession stages (from 5 years old to primary forest). The main objective was to create a model to estimate forest biomass using remote sensing data. Several mathematical models were evaluated. These models used the original bands from SPOT satellite imagery and vegetation indices such as SAVI, MSAVI, GEMI and NDVI. The equation that presented the best fit was B = 458.575 * η, where η is [2 (NIR-R) NIR +1.5 +0.5 R] / (NIR + R +0.5), NIR is the near infrared band, and R is the red band from a SPOT image. The model had a coefficient of determination of 0.802 with a CV% of 52.750. The main achievement of the research was to propose a methodology to probe and create models of biomass estimation using satellite images. The main limitation found was the use of an image with low spectral resolution.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2011
Keywords: Satélites; Parcelas; Modelos; Carbono neutral; Emisiones; Deforestación